Merleau-ponty e a medicalização da existência: por uma fenomenologia do corpo próprio - SANTOS, Neemyas Kerr Batalha dos (2017)
The present research proposes to discuss the topic of the medicalization of existence taking as a perspective the phenomenology of Maurice Merleau-Ponty. Here medicalization is characterized by the assumption that all issues related to existence and even illness and suffering can be sufficiently addressed by exclusively pharmacological interventions. From this context, our main objective is to thematize the conditions of possibility of psychopharmacotherapy as a first and only way for the treatment of mental and behavioral disorders. Following Merleau-Ponty's philosophical tradition we have chosen to employ a methodology that includes a model of phenomenological as well as hermeneutic research. Phenomenological because we could not dispense with medicalization as a phenomenon, that is, in the way in which it presents itself to us. Therefore, an effort is made here so that the medicalization might be understood in this research as a phenomenon before being analyzed as a problem. On the other hand the research also resorts to a hermeneutical look when it focuses on the two works chosen for the study, namely, The Structure of Behavior and Phenomenology of Perception. The main justification for choosing these works is that they have the peculiarity of belonging to a single movement. In both there is the objective of understanding the relations between consciousness and nature, between the organism and the environment, and between the body and itself. Notwithstanding this uniformity we find in the first, elements for a critique of the notion of behavior. Such criticism guided our understanding of behavior as Gestalt, and this is the understanding that leads us in the second work to a critique of the classical notion of sensation. Throughout the two works there is a thread that implicitly or explicitly justifies each of these criticisms: it is the subject of perception. The perception discussed by Merleau-Ponty is of particular importance to our research because it is through it that we can speak of a body that is not only the object body (Körper / Objectif), but the one's own body (Leib / Corps Proper or Corps Vécu). It is to this body itself, it is to this phenomenological body that we submit the subject of the medicalization of existence. Considering that mental and behavioral disorders are supposed to belong to a psychological order, how do we come to believe that there is an isomorphism between this order and the pharmacological targets of psychotropics? The main results of our research suggest that there is no such isomorphism. That the language of the body, be it normal or pathological, is not restricted to a simple translation of neurophysiological events, but to an expressive power of existence whose principle is not only to reveal suffering but also consists in the desire of being understood by others. It is because of the need for this therapeutic route that we find no attempt to summarize the treatment for such disorders to a simple chemical intervention in the nervous system.